Evolution and stability of cosmic string loops with Y-junctions - Bevis, Neil; Copeland, Edmund J.; Martin, Pierre-Yves; Niz, Gustavo; Pourtsidou, Alkistis; Saffin, Paul M.; Steer, D.A. (American Physical Society, 2009)
We study the evolution of non-periodic cosmic string loops containing Y-junctions, such as may form during the evolution of a network of (p,q) cosmic superstrings. We set up and solve the Nambu-Goto equations of motion for a loop with junctions, focusing attention on a specific static and planar initial loop configuration. After a given time, the junctions collide and the Nambu-Goto description breaks down. We also study the same loop configuration in a U(1)xU(1) field theory model that allows composite vortices with corresponding Y-junctions. We show that the field theory and Nambu-Goto evolution are remarkably similar until the collision time. However, in the field theory evolution a new phenomenon occurs: the composite vortices can unzip, producing in the process new Y-junctions, whose separation may grow significantly, destabilizing the configuration. In particular, an initial loop with two Y-junctions may evolve to a configuration with six Y-junctions (all distant from each other). Setting up this new configuration as an initial condition for Nambu Goto strings, we solve for its evolution and establish conditions under which it is stable to the decay mode seen in the field theory case. Remarkably, the condition closely matches that seen in the field theory simulations, and is expressed in terms of simple parameters of the Nambu-Goto system. This implies that there is an easy way to understand the instability in terms of which region of parameter space leads to stable or unstable unzippings.